Erosive wear characteristics of high-chromium based multi-component white cast irons. (July 2021) - Purba, Riki Hendra; Shimizu, Kazumichi; Kusumoto, Kenta; Todaka, Takayuki; Shirai, Masato; Hara, Hiroya; Ito, Jun
Abstract: Erosive wear characteristics of (18 and 27) wt.% Cr based multicomponent (3 wt% V, Mo, W, and Co) white cast iron have been systematically investigated with three conditions: as-cast (AC), as-quenched (Q), and as-quenched tempered (QT). The result shows that Q specimens has the better erosive wear resistance compared to AC due to the transforming of the austenite matrix to be martensite and precipitation of secondary carbide. However, the erosive wear resistance of Q specimens was slightly reduced by the tempering process due to a significant increment of M7 C3 carbide fracture toughness. Therefore, it can be concluded that the excessive Cr addition can be a negative factor on erosive wear-resistance in heat-treated condition and the tempering process should be ignored. Highlights: Erosive resistance of as-cast was increased as increasing the Cr addition and after applying heat treatment process. Erosive wear resistance slightly decreased when conducting the tempering compared to as-quenched. Secondary carbide can negatively influence erosive wear resistance when its volume fraction over the threshold. Microstructure and fracture toughness of the main carbide played as important factors in the erosion performance.